Comparative Outcomes of Pulpotomy in Mature Molars with Irreversible Pulpitis: A Non-Randomized Trial Evaluating Calcified and Non-Calcified Pulp Chambers - Farhadi, Aida; Safarzadeh , Anahita; Nekouei , Amir Hossein; Sabeti , Mohammad; Manochehrifar , Hamed; Shahravan, Arash (Iranian Endodontic Journal, 2024)
Introduction: This non-randomized clinical trial investigated the outcomes of full pulpotomy in adult molars with irreversible pulpitis, comparing those with calcified and non-calcified pulp chambers over 6 and 12 months. Materials and Methods: A total of 101 adult permanent molars with irreversible pulpitis, in individuals over 12 years old, were categorized based on pulp chamber calcification observed in radiographic images by two endodontists. Subsequently, full pulpotomy procedures were performed, achieving hemostasis, and applying a 2 mm layer of calcium-enriched mixture (CEM) cement as a pulp covering agent. After 48 hours, the setting of the CEM cement was verified, followed by the application of a layer of resin-modified glass-ionomer. The tooth was then restored using amalgam. Clinical and radiographic evaluations were conducted at 6-month and 1-year follow-ups by blinded endodontists. Success rates were compared using Fisher's exact test and logistic regression tests with a significance level of 0.05. Results: Among the 97 patients with 6-month and 1-year follow-ups, all achieved clinical success. Radiographic success rates were 99% at 6 months and 96.9% at 1 year, regardless of pulp calcification. In the 6-month follow-up, success rates were 98.07% for non-calcified pulp chambers and 100% for calcified pulp chambers. At the 1-year follow-up, success rates were 96.1% and 97.8%, respectively. Statistical analysis showed no significant difference in radiographic success rate between the two groups at both follow-ups (P>0.05). Conclusions: Full pulpotomy using CEM cement is a successful treatment for adult permanent teeth with calcified and non-calcified pulp chambers presenting signs and symptoms of irreversible pulpitis up to a 1-year follow-up. This study provides compelling evidence that vital pulp therapy can be effectively employed in the pulpotomy of calcified teeth, at least in the short term.